Self-Defense in Criminal Law: Examining Limitations and Implications for Criminal Liability - Auzan Wafi; Hery Firmansyah (JURNAL USM LAW REVIEW, 2025)
This research aims to examine the legal limitations in the application of excessive self-defense (noodweerexces) and its implications for criminal liability in the Indonesian criminal law system. The urgency of this study stems from inconsistencies in judicial practice regarding the interpretation of reasonable limits in self-defense cases, creating legal uncertainty and potential injustice. This research employs a normative juridical method examining legal regulations, theories, principles, and court decisions related to justification and pardon in Indonesian criminal law. The findings indicate that the application of excessive self-defense requires particular attention to avoid violating fundamental principles of justice, with both objective and subjective evaluations necessary to ensure fair law enforcement. The study reveals that variations in judicial decisions necessitate clearer guidelines to ensure legal certainty, while psychological factors of perpetrators significantly influence considerations in noodweerexces assessments. This research contributes new insights by specifically integrating the analysis of objective legal standards with subjective psychological states in criminal liability determination, filling the gap left by previous studies that examined these aspects separately. The study recommends the development of standardized judicial guidelines through Supreme Court circular letters (SEMA) and mandatory training for judges on psychological assessment in self-defense cases, as well as the incorporation of forensic psychology experts in the judicial process for noodweerexces cases.